Action of nicotine and ovariectomy on bone regeneration after tooth extraction in rats - Ribeiro Machado, Giscard Jose [UNESP]; Damasio Dias, Sheila Monica [UNESP]; Bosco, Álvaro Francisco [UNESP]; Okamoto, Tetuo [UNESP]; Bedran de Castro, João Cesar [UNESP]; Dornelles, Rita Cássia Menegati [UNESP] (W B Saunders Co-elsevier Inc, 2010)
Purpose: The purpose of this study was to evaluate the effects of nicotine and ovariectomy on alveolar bone regeneration after exodontias in rats.Materials and Methods: For 30 days, sham ovariectomized (OVX)/NaCl, sham OVX/nicotine, OVX/NaCl, and OVX/nicotine animals were given 2 daily injections of saline or hemisulfate of nicotine. After this period, exodontic procedures were carried out and treatment continued up to the time of euthanasia on clays 7 and 14 when the alveoli were removed for further analyses.Results: The data confirmed that nicotine significantly delays the alveolar regeneration process after dental extraction in rats and showed that the association of nicotine with ovariectomy exacerbates these results.Conclusion: These results indicate that nicotine potentiated the effect of estrogen deficiency on bone regeneration induced by ovariectomy. (c) 2010 American Association of Oral and Maxillofacial Surgeons Oral Maxillofac Surg 68:2675-2681, 2010